Perancangan User Experience Aplikasi Jasa Pengiriman Kendaraan Bermotor menggunakan Metode Pendekatan User Centered Design (Studi Kasus: Cakwar888) - Mohammad Lukman Wibowo; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Cakwar888 is a premium delivery service specializing in the delivery of goods and motorcycles. Cakwar888 faces obstacles in the ineffectiveness of operational activities and communication with customers. Currently, operational activities and communication with customers are carried out through Instagram and WhatsApp. Customers have to wait for a reply to get information and services. This causes the services provided to be less than optimal. This study aims to design the user experience of a motorized vehicle delivery service application. Mobile applications have the potential to solve communication problems with customers, support operational activities, improve brand identity, and increase customer satisfaction. To produce an application design that meets user needs, a user centered design (UCD) approach is used which involves the user in the design process. The testing and evaluation phase is carried out using usability testing and a user experience questionnaire. Usability testing was conducted on 6 respondents. The usability test results on the effectiveness aspect got 96.43% results, the efficiency aspect got 0.085 goals/sec, the satisfaction aspect got 88.75 results, including in grade A+, best imaginable adjective, and acceptable category. User experience testing was conducted on 20 respondents. The user experience test results on the attractiveness aspect got 2.20 results, the perspicuity aspect got 2.21 results, the efficiency aspect got 2.34 results, the dependability aspect got 2.11 results, the stimulation aspect got 2.40 results, and the novelty aspect got 2.18 results.